1996
DOI: 10.1016/s0920-5632(96)00472-0
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization in light-cone gauge: how to do it in a consistent way*

Abstract: We summarize several basic features concerning canonical equal time quantization and renormalization of Yang-Mills theories in light-cone gauge. We describe a "two component" formulation which is reminiscent of the lightcone hamiltonian perturbation rules. Finally we review the derivation of the one-loop Altarelli-Parisi densities, using the correct causal prescription on the "spurious" pole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…= means equality in the sense of the theory of distributions. It was shown that the free gluon propagator supplied with the ML pole prescription can be directly derived following the equal-time quantization procedure and is compatible with well-established results at least up to the O(α s )-order [11,15,19]. The main difference between the q − -independent prescriptions and the ML one (13) originates in the different situation of poles in the q 0 plane, as it is shown and explained in Fig.…”
Section: Structure Of Paths In Transverse-momentum-dependent Parton Dsupporting
confidence: 70%
“…= means equality in the sense of the theory of distributions. It was shown that the free gluon propagator supplied with the ML pole prescription can be directly derived following the equal-time quantization procedure and is compatible with well-established results at least up to the O(α s )-order [11,15,19]. The main difference between the q − -independent prescriptions and the ML one (13) originates in the different situation of poles in the q 0 plane, as it is shown and explained in Fig.…”
Section: Structure Of Paths In Transverse-momentum-dependent Parton Dsupporting
confidence: 70%
“…Note also that the loop-momentum does not bear a large transverse component -see, [9] for details.] Thus, in the hadron frame, QCD effectively splits into two "one-dimensional" theories (see, for instance, [20] and references cited therein). The term "one-dimensional" reflects the fact that the fields Q ± move only along the light-rays p ± This situation may look deceptively simple but in reality it is more complicated because of gluon exchanges between the quark fields.…”
Section: Drell-yan Process and Scetmentioning
confidence: 99%
“…The rules in the four-component formulation are instead the standard ones in light-cone gauge. Renormalization can here be proved following general theorems and then translated in the two-component formulation [13].…”
Section: The Bridge Identitiesmentioning
confidence: 99%
“…( 14), with differentiations with respect to transverse sources, giving rise to bridge identities (BI) between two-and four-component formulations. Those identities, proposed for QCD in [13], can be straightforwardly generalized to the SYM N =4 case at hand. They allow to express Green functions with some non-transverse external lines in terms of purely transverse Green functions.…”
Section: The Bridge Identitiesmentioning
confidence: 99%
See 1 more Smart Citation